MEDIA AJAR AUDIO VISUAL UNTUK PENINGKATAN LITERASI SISWA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Endang Purwasari; Rian Prasetya Yunanto; Yuditia Leo Andhika (Institut Seni Indonesia Surakarta, 2024)
The Indonesian Art Institute of Surakarta is one of the institutions that focuses on developing art science and carries the spirit of art for society. So, in community service activities, in this case, the art scheme, there needs to be involvement from the campus in the community. The PKM that will be held focuses on improving shooting techniques, and image and sound editing. This idea stems from the needs of schools that require updates in audio-visual teaching media that align with the implementation of the Independent Curriculum. Teachers are required to be technologically literate and at the same time keep up with the times when demands are increasingly high. Students can no longer be treated as part of the old learning model because generations Z and Alpha have their characteristics. For this reason, teachers need to improve their skills, especially in terms of presenting material in teaching and learning activities in the classroom. Apart from that, this ability needs to be given to teachers so that it can be applied as a solution to problems faced by other schools, including making school profile videos. The aim of this PKM activity is of course to provide training to teachers so that teacher knowledge and skills increase. Audiovisuals can no longer be separated from the daily lives of today's society. So, educators must also keep pace with this development. This activity program targets outputs in the form of scientific articles and audio-visual works of art submitted by KI to support the main performance indicators (IKU) of higher education. The continuation of this activity program is believed to have increased the teachers' abilities in presenting audio-visual material and abilities in making videos. The output of this PKM activity includes scientific articles published in periodic journals, mass media publications, KI, and exhibitions